ANALISIS PENGARUH DEBT TO ASSET RATIO (DAR) DAN DEBT TO EQUITY RATIO (DER) TERHADAP RETURN ON EQUITY (ROE) PADA PT METRODATA ELECTRONICS TBK TAHUN 2011-2018 - Yelnim .; Poni Yanita (Jurnal Ekonomi Sakti, 2020)
This study aims to analyze the influence of Debt To Asset Ratio (DAR) and Debt To Equity Ratio (DER) to Return On Equity (ROE) at PT.Metrodata Electronics, Tbk Year 2011-2018 both partially and simultaneously. Data analysis using multiple linear regression and coefficient of determination. The data used in this research is secondary data. Data analysis method in this research is descriptive quantitative and descriptive qualitative. The result of analysis shows the regression equation ROE = 0,435 0,263DAR 0,092DER. There is a significant influence Debt To Asset Ratio (DAR) and Debt To Equity Ratio (DER) to Return On Equity (ROE) at PT Metrodata Electronics, Tbk Year 2011-2018 simultaneously this is proved by Fhitung> Ftabel or 12,902> 4,0661. There is partially significant influence Debt To Asset Ratio (DAR) to Return On Equity (ROE) At PT Metrodata Electronics, Tbk Year 2009-2016 is proved by t count> t table 8,291> 2,3060. There is partially significant influence Debt To Asset Ratio (DER) to Return On Equity (ROE) At PT Metrodata Electronics, Tbk Year 2011-2018 is proved by t count> t table 7,662> 2,3060.